Late Vision: Processes and Epistemic Status - Raftopoulos, Athanassios (Frontiers in Psychology, 2011)
In this paper, I examine the processes that occur in late vision and address the problem of whether late vision should be construed as a properly speaking perceptual stage, or as a thought-like discursive stage. Specifically, I argue that late vision, its (partly) conceptual nature notwithstanding, neither is constituted by nor does it implicate what I call pure thoughts, that is, propositional structures that are formed in the cognitive areas of the brain through, and participate in, discursive reasoning and inferences. At the same time, the output of late vision, namely an explicit belief concerning the identity and category membership of an object (that is, a recognitional belief) or its features, eventually enters into discursive reasoning. Using Jackendoff’s distinction between visual awareness, which characterizes perception, and visual understanding, which characterizes pure thought, I claim that the contents of late vision belong to visual awareness and not to visual understanding and that although late vision implicates beliefs, either implicit or explicit, these beliefs are hybrid visual/conceptual constructs and not pure thoughts. Distinguishing between these hybrid representations and pure thoughts and delineating the nature of the representations of late vision lays the ground for examining, among other things, the process of conceptualization that occurs in visual processing and the way concepts modulate perceptual content affecting either its representational or phenomenal character. I also do not discuss the epistemological relations between the representations of late vision and the perceptual judgments they ‘support’, or ‘guide’ or ‘render possible’ or ‘evidence’ or ‘entitle’. However, the specification of the epistemology of late vision lays the ground for attacking that problem as well.